2012
DOI: 10.1063/1.4721654
|View full text |Cite
|
Sign up to set email alerts
|

Influence of flow rate on different properties of diamond-like nanocomposite thin films grown by PECVD

Abstract: Diamond-like nanocomposite (DLN) thin films were deposited on pyrex glass substrate using different flow rate of haxamethyldisiloxane (HMDSO) based liquid precursor with nitrogen gas as a glow discharged decomposition by plasma enhanced chemical vapor deposition (PECVD) technique. The significant influence of different precursor flow rates on refractive index and thickness of the DLN films was measured by using spectroscopic filmatrics and DEKTAK profilometer. Optical transparency of the DLN thin films was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The Si-H species probably arise from the recombination reactions in the gas phase between the dissociated monomer and carrier gas. It was proposed that the Si-H may result from the cleavage of the Si-CH 3 group [36] or as a result of HMDSN byproduct reactions forming radicals containing Si-H bond. C-H n peak is well pronounced showing that carbon is bonded with hydrogen in the films.…”
Section: Resultsmentioning
confidence: 99%
“…The Si-H species probably arise from the recombination reactions in the gas phase between the dissociated monomer and carrier gas. It was proposed that the Si-H may result from the cleavage of the Si-CH 3 group [36] or as a result of HMDSN byproduct reactions forming radicals containing Si-H bond. C-H n peak is well pronounced showing that carbon is bonded with hydrogen in the films.…”
Section: Resultsmentioning
confidence: 99%
“…[30] The CO 2 vibration occurs in the 2,300-2,370 cm −1 region. [31] A wide absorption peak at 2,800-3,000 cm −1 indicates to a relatively high hydrogen content in the coating. This wide absorption band is a superposition of various stretching vibrations of C H bond, and can be deconvoluted into individual peaks corresponding to sp 3 CH 2 (asymmetrical-2,850 cm −1 ); sp 3 CH 3 (symmetrical-2,870 cm −1 ); sp 3 CH 2 (asymmetrical-2,925 cm −1 ); sp 3 CH 2 (olefinic-2,950 cm −1 ); and F I G U R E 5 Fourier transform infrared (FTIR) spectra for polypropylene before (black lines) and after (red lines) sterilization [Color figure can be viewed at wileyonlinelibrary.com] sp 3 CH 3 (asymmetrical-2,960 cm −1 ) bonds.…”
Section: F I G U R Ementioning
confidence: 99%
“…Beeman et al (21) suggested that the shift in G band toward the lower frequency is due to the increase of sp 3 -bonded atomic sites in amorphous carbon films. The I D /I G ratio and FWHM have been used as graphitization indication of the structure of carbon-based materials (22). It is evident from the table that I D /I G ratio is changing with the gas concentration.…”
Section: Synthesis Of Ns-carbon Films Deposited By Mw Pecvd Techniquementioning
confidence: 99%